From Novice to Expert: Exploring the Relationship between Information Literacy Threshold Concepts and Epistemological Development - Folk, Amanda (Communications in information literacy, 2025)
The Framework for Information Literacy for Higher Education articulates the ways of thinking, knowing, and doing that are valued in the academic community. Prior to the Framework, several scholars explored the potential relationship between information literacy and epistemological development, or the ways in which learners develop their understanding of and positionality to knowledge creation. However, the intersections of information literacy and epistemological development have been underexamined in the era of the Framework. In this article, I analyze the Framework through the lens of two epistemological development models, the Epistemological Reflection Model (Baxter-Magolda, 1992) and Reflective Judgement Model (King & Kitchener, 1994), to identify the stages at which learners might need to be in terms of epistemological development to begin the journey of crossing information literacy thresholds. While the Framework makes transparent expert ways of thinking and acting, it does not provide details about how to support learners’ development of these understandings.